Oskar Schindler Righteous gentile - Roberts, Jeremy (New York The Rosen Publishing Group, INC, 2000)
Tells the story of Oskar Schindler and his role in saving more than 1,000 Jews.
Includes bibliography references and Index
12 years and up
Keywords: Schindler, Oskar -- 1908-1974; Righteous Gentiles in the Holocaust; World War -- Jews -- Rescue -- 1939-1945; Holocaust, Jewish -- (1939-1945); Righteous Gentiles in the Holocaust; World War -- Jews -- Rescue. -- 1939-1945; Holocaust, Jewish -- (1939-1945)